Ekpresi Lisan “Karang Awake Tandurin”: Bahasa Bali Sebagai Wahana Domain Budaya Tak Benda - Ida Bagus Rai Putra (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
This research examines “Karang Awake Tandurin”, the oral expression of the Balinese people, which is the domain of intangible culture. Cultural expressions taken from the work of Ida Pedanda Made Sidemen from Griya Intaran Sanur. This excerpt from the text Karang Awake Tandurin is published in the Traditional Balinese Literary work Geguritan Selampah Laku, a Balinese work that was composed and written by himself and tells the personal life history of Ida Pedanda Made Sidemen in Bali Script. This research used a post-structural approach from critical theories. The theories used were Jauss’ reception theory, Pierce’s semiotic theory, and Barthes’ mythology theory. The meaning entities of the Balinese words ‘karang’, ‘awak’ and ‘tandurin’ actually both stand alone, however in life, the use of the three depends on each other, in humans’ relationship with nature and agrarian culture. ‘Tandurin’ is a representation of agricultural activities, ‘karang’ is a representation of nature, and ‘awak’ is a representation of humans. Delve into yourself, understand yourself, reflect on it to its roots, and your perception will become higher. Melting into and becoming the idea of Ida Pedanda Made Sidemen invites every reader to look inside themselves and no longer look elsewhere to start simple life